METHODOLOGICAL APPROACHES TO EVALUATION OF EFFICIENCY OF IMPLEMENTATION OF DIGITALIZATION MANAGEMENT INSTRUMENTS IN AGRICULTURAL ENTERPRISES - RUDENKO, M. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The methodological approaches to evaluating the effectiveness of the implementation of management digitalization tools in agricultural enterprises have been developed in the article.Differentiation of agricultural enterprises depending on the size of the land bank has been carried out. The periods of realization of digitization tools are analyzed and their potential impact on the results of economic activity of agricultural enterprises has been assessed. An analysis of the implementation of digitization tools and an assessment of their potential impact on the results of economic activity often selected for in-depth study of agricultural enterprises.The hypotheses proposed by the author have been confirmed: 1) as a result of the implementation of digitalization tools for the management of agricultural enterprises, the structure of operating costs in subsequent periods changes, the share of depreciation increases and the shares of material costs and wages decrease; 2) the implementation of an investment project related to the use of digital technologies leads to increased economic efficiency and operational profitability.An analysis of the use of digitalization tools in agricultural enterprises, which suggests that in most cases confirms the above trends, but it should be noted that the use of digitalization tools occurred during the economic crisis caused by non-economic factors, accompanied by a devaluation of the national currency and had diverse the nature of the impact on the performance of agricultural enterprises. These conclusions will be used to form scientific and practical proposals for the implementation of digitization tools in agricultural enterprises and develop directions for their impact on the development of the national economy, rural areas, and improve the welfare of citizens.
Keywords: digitization tools; agricultural enterprises; management; efficiency assessment; cost structure; profitability